2022
DOI: 10.3389/fevo.2022.883020
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Volatiles From Push-Pull Companion Crops Repel Fall Armyworm and Attract Its Parasitoids

Abstract: Fall armyworm, Spodoptera frugiperda, is a serious invasive pest in Africa but “Push-Pull” companion cropping can substantially reduce infestation. Here, we elucidate the underpinning chemical ecology mechanisms. We hypothesized that companion crop volatiles repel herbivores (push) while attracting natural enemies (pull). Headspace volatiles collected from companion plants (Desmodium intortum, Desmodium uncinatum, Brachiaria Mulato II) were used in bioassays and electrophysiological recordings with S. frugiper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 56 publications
3
29
4
1
Order By: Relevance
“…The moth prefers undamaged maize plants to avoid competitors and natural enemies for their offspring. Furthermore, a recent study conducted by Sobhy et al 28 found that female S. frugiperda moths were more attracted to the maize odours than the companion crop desmodium volatiles in a wind tunnel bioassay.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The moth prefers undamaged maize plants to avoid competitors and natural enemies for their offspring. Furthermore, a recent study conducted by Sobhy et al 28 found that female S. frugiperda moths were more attracted to the maize odours than the companion crop desmodium volatiles in a wind tunnel bioassay.…”
Section: Discussionmentioning
confidence: 97%
“…reported low S. frugiperda infestation in Colombia when maize was intercropped with beans. Similarly, climate‐adapted push–pull intercropping technology, initially developed for stemborers and striga weed management, significantly reduced S. frugiperda infestation in East African smallholder farming systems 28,59 …”
Section: Discussionmentioning
confidence: 99%
“…Since the database exports in 2021, two additional papers were published about the volatile emissions of desmodium plants (silverleaf desmodium, D. uncinatum and greenleaf desmodium, D. intortum) in PPT systems. While one of these confirmed the presence of volatiles such as β-ocimene, β-caryophyllene and α-pinene in glasshouse measurements, [8] the other (still a preprint at the time of writing) found very low release rates of volatiles from the desmodium intercrop in both glasshouse and field collections. [31] Notably, the first of these publications reports on multiple volatiles which previously had not been linked to push-pull systems (see Supplementary Information Table SI2): (S)-linalool, 1-octen-3-ol, 3-octanone, (E, E)-allo-ocimene and α-copaene were identified pounds in contact with the sensor.…”
Section: How Field Measurements Of Chemistry Could Contribute To Push...mentioning
confidence: 66%
“…(silverleaf or greenleaf desmodium) was furthermore found to be less attractive to fall armyworm (Spodoptera frugiperda) moths in wind tunnel assays, and to reduce oviposition by moths under laboratory conditions, compared to maize volatiles alone; while parasitoid wasps (Cotesia icipe and Coccygidium luteum) were attracted to volatiles from green and silverleaf desmodium, and Brachiaria cv Mulato II, in laboratory olfactometer assays. [8] Recently, field tests of a 'third-generation' push-pull system were reported, using the creeping beggarweed D. incanum as a desmodium intercrop, which benefits from more reliable seed production in Kenya and good drought tolerance; and Brachiaria cv Xaraes as the trap crop, which was rated highly by farmers for drought tolerance as well as biomass yield, and resistance to spider mites. [9] Given its substantial success in east Africa and recent introductions in other African regions, the cereal system described above is one of the best-studied PPT systems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, botanical extracts from Melia volkensii L, Azadirachta indica Juss, Schinnus mol L and Phytolacca dodecandra L. displayed antifeedant activity with larval mortality of more than 90% ( Sisay et al, 2019 ; Jaoko et al, 2021 ). As a versatile option, PPT improves the aboveground and belowground plant environment to enhance the plant while making it less suitable for S. frugiperda ( Khan et al, 2018 ; Sobhy et al, 2022 ) and possesses a convincing trait to act with RNAi. In other words, the importance of combining different control strategies is signified to improve the insecticidal activity of bio-options and prevent pest resistance emergence ( Wang et al, 2017 ; Jaoko et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%